Analisis Penerapan Batas Usia Pesawat Cessna 402b Untuk Transport Category - Raden Yunus Ardianto; Freddy Franciscus; Wahyuni Tri Utami (FTK UNSURYA, 2020)
Many causes of aircraft accidents one of which is the failure of the aircraft to operate normally due to the age of the aircraft that is old. Stipulation of aircraft age restriction regulations are applied to reduce the number of aircraft accidents. The aircraft owned by Whitesky Aviation, the Cessna 402B is an aircraft used for aerial photography activities. Age restrictions on aircraft that are prohibited from operating are 45 years. Calculation of flight hours of the Cessna 402B according to current data records if an estimate is made when reaching the age of 45, the condition of the aircraft is still in good condition. So that age-limiting regulations are not appropriate to apply if applied to aircraft that only have low flight hours. At the writing of this final project aims to determine the influence of the age of the Cessna 420B on operational and maintenance and age limits in accordance with the comparison of maintenance schedule according to Flight Hours and Flight Cycle. And in low utilization operations there is no difference in aircraft operations based on aircraft age, aircraft utilization does not affect the number of maintenance according to the calender time and the age limit of the aircraft has not been reached so that it still has a lot of remaining life. PK-WLW aircraft have a remaining life of 29882.4FH and PK-WLY aircraft have a remaining life of 31405.2FH